AKSES MASYARAKAT MISKIN TERHADAP PROGRAM KELUARGA HARAPAN DAN BANTUAN PANGAN NON TUNAI - Zulvitri, Aisyah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The high number of poor people in Malang City is of course the government's obligation to provide assistance to help meet the basic needs of households in Malang City. Government assistance such as PKH and BPNT have also become assistance owned by the people of Malang City which are obtained in cash and non-cash. According to BPS, the community poverty level is measured based on the food and non-food poverty lines. However, there are still many people who are financially capable but still receive social assistance. Malang City itself has a poverty line of IDR 570,238 per capita per month per 2021. The selection of assistance provided is based on fulfilling government criteria. As the criteria to be examined are the effect of poverty, employment, place of residence and number of family members on PKH and BPNT receipts. This research was conducted with a quantitative descriptive method using binary logistic regression data analysis method. With the results of the study proving that only the variable number of family members has a significant effect on PKH acceptance. Meanwhile, none of the variables affected BPNT revenue. This can be taken into consideration in the process of providing assistance so that it is right on target.